The effects of bacterial leaching on metal partitioning in sewage sludge - Lombardi, Ana T.; Garcia, Oswaldo Jr.; Menezes, Waldenir A. N. (Springer, 2006)
The partitioning of Mn, Al, Zn, Cu and Ti ions in municipal sewage sludge was investigated before and after bioleaching processes effectuated by Acidithiobacillus ferrooxidans and Acidithiobacillus thiooxidans. Oxidation reduction potential increase and pH decrease were obtained as a result of bacterial activity. A less pronounced and constant decrease was obtained with A. ferrooxidans, whereas A. thiooxidans presented a lag phase before a steep pH decrease. Metal solubilization was accomplished in experimental systems supplemented with energy source, Fe2+ for A. ferrooxidans and S-0 for A. thiooxidans. Solubilization efficiency differed for each metal except for Al, and was relatively similar for either organism. Metal partitioning was conducted using five-step sequential extraction procedure before and after the bioleaching. The results indicated that Zn and Mn ions were mostly associated with the organic fraction, whereas Cu, Al and Ti ions with the sulphide/ residue fraction. The bioleaching process caused prompt solubilization of metals mostly associated with the more labile fractions (exchangeable, adsorbed and organically bound metals), whereas those associated to the less labile ones (EDTA and sulphide/residue fractions) were exchanged towards more labile fractions.
Keywords: A. ferrooxidans; A. thiooxidans; bioleaching; metal partitioning; sewage sludge; bacterial leaching